Determinants of Television Media Libraries’ Use, Collections, and Services among the Television Media Professionals in Bengaluru - Kumara, Prasanna; Divyananda, K. (DESIDOC Journal of Library & Information Technology, 2017)
The purpose of this study is to examine the utilisation of television media libraries use, resources and services among the media professional working in various television channels at Bengaluru. Based on this background, a survey method has been adopted and well-structured questionnaire was distributed to collect relevant data about usage behaviour by the media professionals. The study covers media professional working at various television media in Bengaluru. Data was collected from 1132 media professionals and final results indicate that minimum usage of the television media libraries is observed in respondents. The overall statistics shows that usage, collections and services of television media libraries as somehow satisfactory. It is found that primary purpose of the media library is archival and not for referral. An effort has been made by the authors to study the ways to accomplish the demands of television media professionals in television media of Bengaluru, Karnataka.